Leisure Activities and Motivational Profiles in Adaptation to Nursing Homes. Issue 3 (13th July 2018) - Altintas, Emin; Guerrien, Alain; Vivicorsi, Bruno; Clément, Evelyne; Vallerand, Robert J.
RÉSUMÉ: Cette recherche étudie les liens entre motivation, participation aux activités de loisirs et adaptation de personnes âgées au centre d'hébergement dans lequel elles vivent. En accord avec la théorie de l'autodétermination, nous avons testé l'hypothèse que les profils les plus autodéterminés présenteront la meilleure adaptation, la plus grande participation aux activités de loisirs at la meilleure satisfaction de vie. Les participants ont rempli des questionnaires évaluant la motivation, la participation aux activités de loisirs ainsi que l'adaptation au centre d'hébergement. Une analyse des profils latents révèle que les profils hautement autodéterminés (score élevé de motivation autodéterminée et faible score de motivation non-autodéterminée) et les profils additifs (motivation autodéterminée et non autodéterminée élevées) ne diffèrent pas significativement alors que les participants aux profils modérés et aux profils faiblement autodéterminés présentent les scores les plus bas d'adaptation au centre d'hébergement, de participation aux activités de loisirs et de satisfaction de vie. ABSTRACT: Based on self-determination theory, this study examined the relationship between leisure activities, motivation, and adjustment to institutional living by older adults who live in nursing homes. We hypothesized that motivational profiles with higher levels of self-determined motivation represent the optimal profiles regarding participation in leisure activities, adaptation to nursing home living, and satisfaction with life. Participants completed questionnaires assessing motivation, leisure activity participation, life satisfaction, and adaptation to the nursing home. Results showed a relationship between the latter three factors. A latent profile analysis based on the different forms of motivation indicated four distinct profiles. Although no differences were found between the high self-determined profile (high self-determined motivation and low non-self-determined motivation) and the additive profile (high self-determined motivation and non-self-determined motivation), participants with a moderate profile and a low self-determined profile reported the lowest levels in leisure activity participation, adaptation to the nursing home, and satisfaction with life.